The Patient-Doctor Relations III Program Curriculum Enhancement analysis, implementation, and evaluation. - Ypil, Ma. Amethyst R.; Melflor A. Atienza, MD, MHPEd (Manila National Teacher Training Center for the Health Professions, University of the Philippines Manila, 2024)
Modifying the PDR III program to improve the effectiveness and relevance of the curriculum began with a stakeholder’s analysis and Merril's Instructional quality profile, which provided information on perceived issues with curricular alignment, teaching-learning strategies, assessment, and evaluation. The PDR III curriculum was streamlined into five attainable program outcomes that align with the institutional goals and the CMO 18 of 2016 guidelines. The curriculum content was explicitly established through a competency analysis, concept mapping, and the formulation of intended learning outcomes for affective, procedural, and cognitive abilities that correspond with department-specific course learning outcomes. In order to enhance patient care and satisfaction, foster professionalism, and ensure accountability, patient safety competencies were integrated into each department. Nonetheless, in order for students to support the new institutional vision of producing transformational physicians and valuing primary healthcare, they must be exposed to the community. This issue was brought to the attention of the Dean, who approved a community rotation, and a MOA was sent to the City Health Officer in August 2023 to allow students to rotate around nearby barangay health centers. (See Appendix N, Letter to City Health Officer) However, in spite of repeated reminders, no feedback has been obtained until now. The instant modifications of teaching-learning strategies brought about by the pandemic were further technology-enhanced. The teachers who used to be technology-challenged were now at ease using it in the classroom. Learning becomes interactive using TED-Ed lecture video files as supplemental learning materials to ensure all learning outcomes are met. Students' portfolios now utilize Google Sites. Students' sense of social responsibility and creativity will be enhanced by health advocacy learning tasks that involve creating infographics based on cases they see in the clinic. The assessment for collaboration and teamwork included a case-based learning group exercise where participants solved case-based scenarios to develop their case diagnosis and management skills. These T-L strategies made the program resilient to the pandemic and other threats to clinical teaching.
Capstone Project